Studi Kajian Kemiskinan, Inflasi dan Pertumbuhan Ekonomi di Sumatera Utara - Samuel Frans Deo; Zuziva Apriliani; M Zakaria Anshori; Dewi Mahrani Rangkuty (Jurnal Kajian dan Penelitian Umum, 2023)
Poverty and inflation are complex and multidimensional economic problems. Therefore, it is necessary to find solutions to overcome or at least reduce the level of poverty and suppress a stable inflation rate. This study aims to analyze the level of poverty and inflation on economic growth. The type of research is descriptive qualitative research with a literature study research method through literature study used secondary data obtained from the North Sumatra Central Bureau of Statistics. The results of this study explained that poverty and inflation greatly affect economic growth. If poverty increases, it means that economic growth conditions are weak and high and unstable inflation is a reflection of economic instability which results in a general and continuous increase in the price level of goods and services.